The Effects of Domestic Violence on the Academic Performance of Pupils: A Case Study of Primary Schools in Laroo Division, Gulu Municipality - OKITE, APIO SARAH (Advances in Social Sciences Research Journal, 2021)
Study findings on the effects of domestic violence on academic performance have shown that individual academic performance levels are affected by a host of factors outside of the classroom including home environments. A cross-sectional study design was adopted where both qualitative and quantitative research approaches were used. Three schools out of 08 and a total of 42 respondents were sampled purposively or randomly to constitute study samples. Questionnaire and interview methods were used to collect primary and secondary data. Quantitative data were analyzed using SPSS V16 while content analysis was used for the qualitative data. A total of 50% of the respondents who are the majority said less concentration span is the effect of domestic violence on the school attendance. The study reveals that majority of the pupils identified to be affected by domestic violence are isolated, depressed and violent as indicated by 58% which affects their class participation. 71% of the respondents said the school performance of pupils deteriorates. The study reveals that 60% of the respondents said poverty is the major cause of high drop out among pupils. It was concluded that high rate of poverty and drunkardness is the major cause of domestic violence and greatly affects the academic performance. It was recommended that the Government should pass ordnances on alcoholism as to reduce on the rate of domestic violence and improve academic performance of pupils from affected families.